The Regional Economic Effects of Military Base Realignments and Closures. Issue 3 (16th April 2018) - Lee, Jim
Abstract : This paper empirically investigates the impact of military base realignments and closures on regional economic activity in light of the 2005 round of Base Realignment and Closure actions. Baseline regressions with county-level data show employment multipliers comparable to those generated from conventional input–output models. However, controlling for possible endogeneity and other regional-specific factors, regressions indicate more tenuous results for spillover effects from the military to the private sector. Only the contractor type of base employment generated economically and statistically meaningful impacts on local employment. In addition, there is strong evidence of asymmetric effects between military buildups and drawdowns.